Regional and Cohesion Policy in Hungary - Horváth, Gyula (Discussion Papers, 1998)
In 20th century Hungarian regional development, apart from the influence of the inner regularities of the economy, economic policy and state regional development policy was influenced by international political decisions that upset the spatial structure of the country and delayed its integration into Europe. Due to the economic policies of the last fifty years and to the settlement structure development initiated in the 1960’s, the spatial structure of the country has changed, its settlement structure has become formally more modern and differences between the major regions have lessened. In spite of the favourable changes, the spatial structure of the country still does not suit the conditions required for the rise of a modern market economy. The increasing social and economic innovations as well as the country’s integration into the European division of labour are hindered by the lack of cohesion and infrastructural connections between the regions and by the underdeveloped character of regional centres. The purpose of the first part of the study is to present the changing regional policy from the 90s, its strategic objectives and priorities, its relationship to sectoral policies, the changing legal regulation and the territorial structure of Fund utilisation. In the second chapter, the author gives an overview of the new era of regional policy beginning with the legislation of 1996, introducing the National Regional Development Concept and the instruments of regional policy. The third chapter examines the EU-compatibility of Hungarian regional policy. In the final part of the study the author considers the most significant tasks to be implemented before EU-accession. He concludes that even though regional policy in Hungary is in a state of flux, as opposed the other East-Central European countries, measures have progressed far beyond the conceptual stage, the institutional infrastructure has been in action, there has been a recent trend to achieve greater compatibility between EU and Hungarian regional policies.